2019
DOI: 10.24875/ric.19002935
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Mineral Density with Chronic Obstructive Pulmonary Disease in Postmenopausal Women

Abstract: Background: Osteoporosis (OP) is common in patients with chronic obstructive pulmonary disease (COPD). The relationship between OP and COPD has been primarily studied in male patients, and few reports are available in postmenopausal women. Objective: The purpose of this study was to investigate the association between bone mineral density (BMD) and COPD in postmenopausal women. Methods: This cross-sectional study included 133 clinically stable female ex-smokers with confirmed COPD, and 31 age-matched "ex-smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A previous study, which recruited post-menopausal women aged ≥50 years with diagnosed COPD and age-matched past smokers, demonstrated that moderate-to-very severe airway obstruction were related to osteopenia and osteoporosis BMD in patients with COPD. 28 Moreover, research conducted using data from the Third National Health and Nutrition Examination Survey reported that severe AL is a risk factor for osteopenia and osteoporosis. 29 We evaluated more participants and FEV 1 /FVC using prebronchodilator spirometry; however, there were no participants with severe or very severe AL and a small number of moderate AL (n=19) and current smokers (n=58).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study, which recruited post-menopausal women aged ≥50 years with diagnosed COPD and age-matched past smokers, demonstrated that moderate-to-very severe airway obstruction were related to osteopenia and osteoporosis BMD in patients with COPD. 28 Moreover, research conducted using data from the Third National Health and Nutrition Examination Survey reported that severe AL is a risk factor for osteopenia and osteoporosis. 29 We evaluated more participants and FEV 1 /FVC using prebronchodilator spirometry; however, there were no participants with severe or very severe AL and a small number of moderate AL (n=19) and current smokers (n=58).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lower FEV 1 /FVC was observed in the OSTA high-risk group; however, this was not signi cantly different among the three groups classi ed according to BMD category, and we found no relationship between FEV 1 /FVC and BMD in this study. A previous study, which recruited postmenopausal women aged ≥ 50 years diagnosed with COPD and age-matched past smokers, demonstrated that moderate-to-very severe airway obstruction are related to osteopenia and osteoporosis BMD in patients with COPD [23]. Moreover, research conducted using data from the Third National Health and Nutrition Examination Survey reported that severe AL is a risk factor for osteopenia and osteoporosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of osteoporosis and fragility fractures can be reduced through healthy lifestyle changes [ 18 , 19 ]. Chronic obstructive pulmonary disease and airway obstruction were also related to bone mineral density in postmenopausal women [ 20 ]. Those symptoms were consistent with the performance of constitutions in deficiency and stasis [ 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%